EFEKTIFITAS PENERAPAN TEKNIK PSIKODRAMA DALAM BIMBINGAN KELOMPOK DAPAT MENINGKATKAN KESTABILAN EMOSI SISWA KELAS X SMK TUNAS WISATA INDONESIA BEKASI - Saifoel Bachrie; Arief Eka Ranjani (Guidance : Jurnal Bimbingan dan Konseling, 2016)
This study focused on the application of psychodrama techniques in group counselingto improve emotional stability at class X SMK Tunas Wisata Indonesia Bekasi. Researchersfocused goal is to determine and disclose as well as to alleviate the problems experienced bystudents through psychodrama methods, both issues that are personal, social, career, andother problems associated with emotions that include improving students emotional stabilityof students through psychodrama techniques and transform negative emotions into positiveemotions of students, so students can better control his emotions.This study design using quantitative research with quasi-experimental methods. And asampling technique in this study using cluster sampling. The population in this study werestudents of class X SMK Tunas Wisata Indonesia Bekasi, amounting to 115 students and 25students of class X Hotel Accommodation chosen as samples.Results from this study show that implementation of psychodrama techniques ingroup counseling is effective to improve students emotional stability. It is known from thecalculation results before and after the introduction of the treatment of students, as well asthrough statistical calculation results expressed as t count> t-table then Ha accepted andrejected H0, t count> t-table = 4.5341> 2.064 then ha accepted. With the confidence level (1-α) 100% = 90%, then there is a significant relationship between the application ofpsychodrama in group counseling techniques to improve emotional stability class X AP-1SMK Tunas Wisata Indonesia.